Офіційний та неофіційний погляд на сучасну українську культурну політику - Хома, І. Я. (Lviv Polytechnic Publishing House, 2016)
Розкрито ставлення до офіційної політики в сфері культури та її наслідків станом на кінець 2013 р. Акцент зосереджено на офіційних даних та думках інтелектуалів та експертів українського громадського суспільства. Euromaidan and dignity revolution, which further continues, clearly show that without change in the national policy of culture change the country will be very difficult. It’s tactics and strategy formation space of life for the citizens of Ukraine, information about Ukrainian and country in the world, formed throughout history and established in today’s harmful and humiliating stereotypes, myths. Obviously the official state culture has long been not satisfied an active, creative part of society. Outside the official data analysis of cultural policy meet in publications, cultural in content, authored by writers, critics, scholars and public figures. Balance cultural processes, that attitude to culture as an important tool strengthening state sovereignty on the political, spiritual, economic and other levels and other levels within Ukraine and abroad ensured civil society. They monitor cultural processes. Among the most notable, sharp and accurate assessments of cultural policy is advisable to allocate positions L. Kostenko, I. Dziuba, O. Zabuzhko, M. Riabczuk and other lesser-known experts. These persons is difficult to accuse of bias. In the article was put goal disclose the relationship to the national cultural policy of the Ukrainian intelligentsia and civil society experts, that are recognized in Ukraine and the world.
Keywords: культурна політика; спадщина; національна пам’ять; громадянське суспільство; cultural policy; heritage; national memory; civil society; 304.4:323(477:4)